2011
DOI: 10.1094/phyto-06-10-0157
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Resistance-Breaking Ability of Different Beet necrotic yellow vein virus Isolates Loaded into a Single Polymyxa betae Population in Soil

Abstract: The genome of most Beet necrotic yellow vein virus (BNYVV) isolates is comprised of four RNAs. The ability of certain isolates to overcome Rz1-mediated resistance in sugar beet grown in the United States and Europe is associated with point mutations in the pathogenicity factor P25. When the virus is inoculated mechanically into sugar beet roots at high density, the ability depends on an alanine to valine substitution at P25 position 67. Increased aggressiveness is shown by BNYVV P type isolates, which carry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…() showed by means of reverse genetics that this amino acid exchange alone is responsible for the induction of Rz1 resistance‐breaking (RB) ability in an European A type strain. Bornemann & Varrelmann () showed that RB strains retained their resistance‐breaking abilities even after loading of another virus‐free soilborne vector population. It was supposed that Rz1 selected for this resistance‐breaking mutation, because another resistance source, Rz2 (Scholten et al ., ), in combination with Rz1 still effectively reduces replication of mutated strains (Liu et al ., ; Pferdmenges et al ., ; Bornemann & Varrelmann, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…() showed by means of reverse genetics that this amino acid exchange alone is responsible for the induction of Rz1 resistance‐breaking (RB) ability in an European A type strain. Bornemann & Varrelmann () showed that RB strains retained their resistance‐breaking abilities even after loading of another virus‐free soilborne vector population. It was supposed that Rz1 selected for this resistance‐breaking mutation, because another resistance source, Rz2 (Scholten et al ., ), in combination with Rz1 still effectively reduces replication of mutated strains (Liu et al ., ; Pferdmenges et al ., ; Bornemann & Varrelmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bornemann & Varrelmann () showed that RB strains retained their resistance‐breaking abilities even after loading of another virus‐free soilborne vector population. It was supposed that Rz1 selected for this resistance‐breaking mutation, because another resistance source, Rz2 (Scholten et al ., ), in combination with Rz1 still effectively reduces replication of mutated strains (Liu et al ., ; Pferdmenges et al ., ; Bornemann & Varrelmann, ). Both Rz1 and Rz2 resistant plants display a phenotype of quantitative resistance (Scholten et al ., ; Heijbroek et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the difference in aggressiveness between BNYVV isolates was found to be independent of the Polymyxa betae vector population (Bornemann and Varrelmann 2011). Tuitert et al (1994) found that the total number of P. betae resting spore clusters formed in roots of partially BNYVV-resistant cultivars and a susceptible cultivar did not differ at 6 and 12 weeks after inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the manifestations of rhizomania on tolerant varieties were reported at several sites (ITB, 2010). This situation was partially explained by the lack of tolerance of some varieties, or higher pressure of the disease, due to one hot and wet spring and a more important presence of the Polymyxa, or even the appearance and increase of virulent pathotypes in the pathogen population (Schmit et al, 2002;Rush, 2003;Bornemann and Varrelmann, 2011).…”
Section: Introductionmentioning
confidence: 99%